Chemogenetic inhibition of Phox2-expressing neurons in the commissural NTS decreases blood pressure in anesthetized spontaneously hypertensive rats - Melo, Mariana Rosso [UNESP]; Voger, Joshua J.; Connelly, Angela A.; Bassi, Jaspreet K.; Colombari, Eduardo [UNESP]; Allen, Andrew M. (Elsevier, 2022)
Interruption of the activity of neurons in the commissural portion of the nucleus of the solitary tract (cNTS) decreases blood pressure (BP) in experimental models of hypertension, such as the spontaneously hypertensive (SH) rat. To examine whether PHOX2B expressing cNTS neurons are involved in maintaining the elevated BP, we used replication-deficient viruses with a modified Phox2 binding site promoter to express the inhibitory chemogenetic allatostatin receptor or green fluorescent protein in the cNTS. Following administration of allatostatin, we observed a depressor and bradycardic response in anesthetized SH rats that expressed the allatostatin receptor. Injection of allatostatin did not affect BP or heart rate (HR) in control SH rats expressing green fluorescent protein in the cNTS. Immunohistochemistry showed that the majority of transduced cNTS neurons were PHOX2B-immunoreactive and some also expressed tyrosine hydroxylase. We conclude that in anesthetized SH rat, the Phox2B expressing cNTS neurons maintain elevated BP.
Keywords: Allatostatin; Blood pressure; Brainstem; Chemogenetics; Hypertension; Nucleus of the Solitary Tract